ECONOMIC VALUE OF WILDLIFE SANCTUARY: A CASE STUDY FROM THE WESTERN GHATS IN KARNATAKA, INDIA - Balasubramanian, Muniyandi (Indonesian Journal of Forestry Research, 2022)
Goods and services of the ecosystem provided by the natural environment have not been considered in terms of their economic value. There are a number of studies that have estimated the economic value of forest ecosystem services in India, but very few studies have estimated these economic values of other important ecosystem services. Biligiri Rangaswamy Temple Wildlife Sanctuary (BRTWLS) is a unique place as a bridge between the Western Ghats and the Eastern Ghats in Karnataka, India. There are 12,500 Soligas (tribal community) living in this area. Non-timber forest products constitute more than 60% of the Soliga household income. A number of studies have been conducted in the BRTWLS. However, there is a lack of studies on the economic value. The primary objective of this study is to estimate the value of ecosystem services provided by BRTWLS. This study has used the market price methods for estimating the value of provisioning services and individual travel cost method for estimating the value of recreation services, while the value of carbon sequestration and soil erosion prevention has been estimated based on secondary data. This study has estimated the total annual value of provisioning, regulating and cultural services of BRTWLS at Rs 23.9 million y-1. The findings of the study will be helpful to the local policy makers to increase the entry fee at the BRTWLS, as it provides valuable ecosystem services and reinvests the same in natural capital to achieve environmental sustainability at the local level.